SPECIALIZED EDUCATIONAL SERVICE (SES) AS A TOOL OF ACCESS IN THE INCLUSIVE PROCESS - Magalhães Araújo, Ana Cristina; Wendel Santana Coêlho, Márcio (Revista Gênero e Interdisciplinaridade, 2022)
The present study aims to discuss and understand the implementation and organization of Specialized Educational Assistance-SEA while tool for accessing the inclusive process in the Brazilian educational system. It examines the organization, the implementation process and the methodology of this new educational model, through the most recent theoretical and legal assumptions. A debate was developed around the characteristics and challenges that permeate special education as a priority service for the inclusive process of students with disabilities, autistic spectrum disorder and high abilities/giftedness in ordinary schools, with a view to meeting their needs, in a so that they can overcome the barriers imposed by the common school and participate in their class with autonomy. The present article favored the qualitative approach and the bibliographic research as a technique. The study was based on national and international legal texts and on the concepts of Mantoan (2010), Glat & Ferreira (2005), Smith (2008), Dorziat (2015), Fávero (2005), Minayo (2001), among others.